A MULTISENSORY MUSEUM AS A MODERN LEARNING ENVIRONMENT: A FINNISH PILOT STUDY AT THE SIBELIUS EXHIBITION IN THE CASTLE OF HÄME - Marja Sirkkola (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
A multisensory environment (MSE) is known as a place where individual’s senses and body awareness are activated or relaxed in various gentle ways through all senses using music and sounds, colors and lights, vibration and movement, tactile objects, smells and tastes in various combinations. However, multisensory environments (MSEs) can also be used as modern learning environments for cultural purposes.